Drought‐induced mortality patterns and rapid biomass recovery in a terra firme forest in the Colombian Amazon - Daniel Zuleta; Alvaro Duque; Dairon Cardenas; Helene C. Muller‐Landau; Stuart J. Davies (Ecology, 2017)
Extreme climatic events affecting the Amazon region are expected to become more frequent under ongoing climate change. In this study, we assessed the responses to the 2010 drought of over 14,000 trees ≥10 cm dbh in a 25 ha lowland forest plot in the Colombian Amazon and how these responses varied among topographically defined habitats, with tree size, and with species wood density. Tree mortality was significantly higher during the 2010–2013 period immediately after the drought than in 2007–2010. The post‐drought increase in mortality was stronger for trees located in valleys (+243%) than for those located on slopes (+67%) and ridges (+57%). Tree‐based generalized linear mixed models showed a significant negative effect of species wood density on mortality and no effect of tree size. Despite the elevated post‐drought mortality, aboveground biomass increased from 2007 to 2013 by 1.62 Mg ha −1 yr −1 (95% CI 0.80–2.43 Mg ha −1 yr −1 ). Biomass change varied among habitats, with no significant increase on the slopes (1.05, 95% CI −0.76 to 2.85 Mg ha −1 yr −1 ), a significant increase in the valleys (1.33, 95% CI 0.37–2.34 Mg ha −1 yr −1 ), and a strong increase on the ridges (2.79, 95% CI 1.20–4.21 Mg ha −1 yr −1 ). These results indicate a high carbon resilience of this forest to the 2010 drought due to habitat‐associated and interspecific heterogeneity in responses including directional changes in functional composition driven by enhanced performance of drought‐tolerant species that inhabit the drier ridges.